Pengaruh Biaya Penyimpanan Terhadap Harga Produk Yang Dijual di PT. Liquid Kencana Abadi (LPPM Universitas HKBP Nommensen, 2025)
This study aims to analyze the extent to which Storage Costs affect Product Prices at PT. Liquid Kencana Abadi. The research method used is a quantitative method with a simple regression analysis approach. Based on the results of the analysis, a determination coefficient value (R²) of 0.315 was obtained, which means that Storage Costs were able to explain 31.5% of product price variations, while the remaining 68.5% was influenced by other factors outside this research model, such as distribution costs, production costs, marketing strategies, and company profit margins. Furthermore, the results of the t-test showed that the significance value of variable X was 0.000 < 0.05 and the t-value calculated was 14.955 > t table 2.052. This proves that the alternative hypothesis (Ha) is accepted, so it can be concluded that Storage Costs have a significant effect on the Product Price. This means that the higher the storage costs borne by the company, the greater the tendency to increase product prices to cover the operational expenses. These findings are in line with the theory and results of previous research that stated that storage costs are an important part of the cost structure that affects the selling price of products. Thus, efficiency in warehouse management, the use of logistics technology, and inventory control are needed so that companies can reduce storage costs, maintain price stability, and increase competitiveness in the market.